Prevalence of Hypothyroidism in Pregnancies and its Obstetric Outcomes - Tabassum Ali, Abroo Bahadur, Bushra Bashir, Tariq Hassan, Benish Ishaq, Muhammad Qasim (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Hypertension, placental abruption, low birth weight, fetal death, and preterm birth are different pregnancy complications associated with clinical thyroid dysfunction. Thyroid dysfunction is common among pregnant women. The aim of the present study was to assess the prevalence of hypothyroidism in pregnancies and its obstetric outcomes. Methodology: This cross sectional study was conducted 164 antenatal women with singleton pregnancy in third trimester at the department of Gynecology and Obstetrics, Hayatabad Medical Complex, Peshawar for the duration of six months from January 2021 to October 2021. All the pregnant women irrespective of parity, socio-economics, and age were enrolled after taking informed consent. All cases of thyroid disorders and having multiple pregnancy were left out. Routinely hematological factors and estimation of TSH, fT3, and fT4 was performed. Fetal and maternal complications were assessed subsequently in patients for thyroid deranged profile. Thyroid disease family and infertility history, level of hemoglobin, menstrual pattern, fetal outcome, and recurrent abortion were the main parameters. SPSS version 21 was used for data analysis. Results: Out of 164 women screened, prevalence of thyroid dysfunction was 41 (25%). The incidence of subclinical hyperthyroidism, subclinical hypothyroidism, and overt hypothyroidism was 13 (7.8%), 6 (3.7%), and 9 (5.4%) respectively. Higher TSH and abnormal fT4 was found in one sample. About 28.5% patients had anemia among over and subclinical hypothyroidism. Hypothyroidism was significantly associated with NICU admission 39.2% (p=0.001), LBW 28.7% (p=0.001), and low APGAR score 23.6% (p=0.039). Comparing hypothyroidism women to euthyroid women, risk of NICU admission, low birth weight, lower APGAR score, and anemia was found 1.3, 5.8, 3.7, and 4.9 times higher. Conclusion: Our study revealed that pregnant women are more susceptible to subclinical hypothyroidism. In the third trimester of pregnancy, the occurrence of subclinical hypothyroidism is 3.7%. Hypothyroidism is associated with pre-eclampsia, anemia, neonatal morbidities, and high caesarean rates.